PENGEMBANGAN SOAL-SOAL OPEN-ENDED POKOK BAHASAN BILANGAN PECAHAN DI SEKOLAH MENENGAH PERTAMA - Mustikasari; Zulkardi; Aisyah, Nyimas (Mathematics Education Journal, 2010)
The research is aimed to: (1) Get the set of open-ended problems which are valid and practical about fraction number in the Junior High School. (2) Find out the potential effects of open ended problems in relation to students’achievement in solving open-ended problems at Junior High School. This research is a developmental research. The respondence of this research are 37 students of seventh grade at SMP Negeri 6 Sekayu. The instrument used for this research is test of open ended problems. All data have been collected was analysed qualitatively. The results show that: (1) This research produces open ended problem about fraction number for students of VII grade which are valid and practical. The validity was judged by validator, where the all validators state that the instrument have been valid based on the content, construct and face. The validity was also judge by validator in the small group. The practicality was shown by the result of validators, which most of students could solve the open-ended problems. (2) The prototype of open-ended problems which were developed has positive potential effect to the result of student achievement, and that is shown by the variety of students’ answers, and the average students’positive category of 2 tests were 79,8%. DOI: 10.22342/jpm.4.2.820